Violência política de gênero: análise das estratégias de enfrentamento do sistema de justiça na defesa da vida das mulheres - Pires, Luiza de Carvalho (2024)
The present research aims to analyze gender-based political violence through the narratives of female deputies from Minas Gerais elected in 2022. The theoretical framework is mobilized based on contributions from authors such as Sylvia Walby (1990), Lena Krook and Juliana Restreppo Sanín (2016), Flávia Biroli (2018), and Marlise Matos (2021). Through qualitative-exploratory research, systematic literature review, documentary analysis, and semi-structured interviews with parliamentarians from different legislative bodies will be used as data collection instruments. With the goal of examining the dynamics, contexts, and variations of gender-based political violence and how the justice system prevents and responds to this issue, the research presupposes that, even after legal achievements, there are difficulties in recognizing and punishing such practices.